Endothelial neuropilin‐2 influences angiogenesis by regulating actin pattern development and α5‐integrin‐p‐FAK complex recruitment to assembling adhesion sites. Issue 8 (27th July 2021) - Benwell, Christopher J.; Taylor, James A. G. E.; Robinson, Stephen D.
Abstract: The ability to form a variety of cell‐matrix connections is crucial for angiogenesis to take place. Without stable anchorage to the extracellular matrix (ECM), endothelial cells (ECs) are unable to sense, integrate and disseminate growth factor stimulated responses that drive growth of a vascular bed. Neuropilin‐2 (NRP2) is a widely expressed membrane‐bound multifunctional non‐tyrosine kinase receptor, which has previously been implicated in influencing cell adhesion and migration by interacting with α5‐integrin and regulating adhesion turnover. α5‐integrin, and its ECM ligand fibronectin (FN) are both known to be upregulated during the formation of neo‐vasculature. Despite being descriptively annotated as a candidate biomarker for aggressive cancer phenotypes, the EC‐specific roles for NRP2 during developmental and pathological angiogenesis remain unexplored. The data reported here support a model whereby NRP2 actively promotes EC adhesion and migration by regulating dynamic cytoskeletal remodeling and by stimulating Rab11‐dependent recycling of α5‐integrin‐ p ‐FAK complexes to newly assembling adhesion sites. Furthermore, temporal depletion of EC‐NRP2 in vivo impairs primary tumor growth by disrupting vessel formation. We also demonstrate that EC‐NRP2 is required for normal postnatal retinal vascular development, specifically by regulating cell‐matrix adhesion. Upon loss of endothelial NRP2, vascular outgrowth from the optic nerve during superficial plexus formation is disrupted, likely due to reduced FAK phosphorylation within sprouting tip cells.